2009
DOI: 10.1111/j.1600-0609.2008.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of WNT signaling effectively induce apoptosis in acute myeloid leukemia cells

Abstract: In a significant proportion of acute myeloid leukemia (AML) cases the canonical WNT pathway is upregulated and targeting the WNT/LEF1 signaling cascade in AML may be a promising approach to develop new treatments for this entity. Recently two compounds (CGP049090 and PFK115-584) have been identified, which specifically inhibit complexation of beta-catenin (CTNNB1) and lymphoid enhancer-binding factor 1 (LEF1) leading to transcriptional inactivation of LEF1 in colon carcinoma cell lines. To evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 46 publications
(67 reference statements)
4
54
0
Order By: Relevance
“…The experiments performed with the pharmacological inhibitor PKF115-584 indicate that at least TCF-4 plays an important role in the regulation of versican, collagen I␣1, and fibronectin expression by airway smooth muscle cells, since this inhibitor disrupts the interaction between nuclear ␤-catenin and TCF-4 (4,47,52). This fits with observations that indicate abundant expression of the TCF-4 transcription factor by mesenchymal cells (7,11).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The experiments performed with the pharmacological inhibitor PKF115-584 indicate that at least TCF-4 plays an important role in the regulation of versican, collagen I␣1, and fibronectin expression by airway smooth muscle cells, since this inhibitor disrupts the interaction between nuclear ␤-catenin and TCF-4 (4,47,52). This fits with observations that indicate abundant expression of the TCF-4 transcription factor by mesenchymal cells (7,11).…”
Section: Discussionsupporting
confidence: 74%
“…To further verify the functional role of ␤-catenin/TCF interactions in TGF-␤ 1 -induced ECM gene expression, we pharmacologically inhibited ␤-catenin signaling by PKF115-584 a compound that disrupts the interaction of the transcriptionally active (nonphosphorylated) ␤-catenin/T-cell factor-4 (TCF-4) complex (4,47,52). In line with the findings obtained with ␤-catenin siRNA, PKF115-584 did not significantly affect basal expression of collagen I␣1 (P ϭ 0.432), fibronectin (P ϭ 0.693), or versican (P ϭ 0.394) but largely attenuated the TGF-␤ 1 -induced expression of these ECM genes (Fig.…”
Section: Tgf-␤ 1 Induces ␤-Catenin Expression In Airway Smooth Musclementioning
confidence: 99%
“…Furthermore, patients with high LEF1 expression should be considered for new molecular directed therapies, especially agents targeting the Wnt pathway 39 or demethylating drugs. 12 Recently, 2 small molecules have been identified that specifically inhibit the LEF1/␤-catenin complex and have shown promising in vitro efficacy in AML cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, 2 small molecules have been identified that specifically inhibit the LEF1/␤-catenin complex and have shown promising in vitro efficacy in AML cell lines. 6,39 Of note, most relapses in B-precursor ALL patients with high LEF1 expression occurred early within the first year of remission, underlining the importance of adapted first-line therapies for this particular high-risk group. As Wnt signaling has been implicated in self-renewal of leukemic stem cells, [40][41][42] early relapse of patients with LEF1 overexpression might reflect a survival advantage of leukemic stem cells because of LEF1 expression.…”
mentioning
confidence: 99%
“…2,33,34 Leukemogenic fusion genes and gene mutations can induce Wnt signaling in AML, aberrant activation of the Wnt effector ␤-catenin has been detected in primary AML samples, and small-molecule Wnt pathway inhibitors are cytotoxic for AML blasts. 3,5,35 Our group previously showed that overexpression of Lef-1 in murine BM leads to disturbed hematopoiesis and, ultimately, to the development of myeloid and lymphoid leukemias. 10 Interestingly, the myeloid leukemias arising in this model originated from a leukemic stem cell with lymphoid characteristics and showed coexpression of lymphoid markers.…”
Section: Lef1 Expression Is Prognostic In Cn-aml 2123mentioning
confidence: 99%